Auditory-vocal integration impairment: New challenges and opportunities for voice assessment and therapy - Adrián Castillo-Allendes; Francisco Contreras-Ruston; Jeff Searl (Revista de Investigación e Innovación en Ciencias de la Salud, 2021)
This reflection paper addresses the importance of the interaction between voice perception and voice production, emphasizing the processes of auditory-vocal integration that are not yet widely reported in the context of voice clinicians. Given the above, this article seeks to 1) highlight the important link between voice production and voice perception and 2) consider whether this relationship might be exploited clinically for diagnostic purposes and therapeutic benefit. Existing theories on speech production and its interaction with auditory perception provide context for discussing why the evaluation of auditory-vocal processes could help identify associated origins of dysphonia and inform the clinician around appropriate management strategies. Incorporating auditory-vocal integration assessment through sensorimotor adaptation paradigm testing could prove to be an important addition to voice assessment protocols at the clinical level. Further, if future studies can specify the means to manipulate and enhance a person’s auditory-vocal integration, the efficiency of voice therapy could be increased, leading to improved quality of life for people with voice disorders.